Real-life comparison of the afatinib and first-generation tyrosine kinase inhibitors in nonsmall cell lung cancer harboring EGFR exon 19 deletion: a Turk Oncology Group (TOG) study - YUMUK, PERRAN FULDEN; BAŞOĞLU TÜYLÜ, TUĞBA (SPRINGER, 2021)
Background The new second-generation tyrosine kinase inhibitors (TKIs) have superior survival outcome and worse toxicity profile when compared with first-generation TKIs according to the results of clinical trials. However, there are limited studies that investigate the efficacy and safety of the new generation TKIs in real-world patients. Thus, we aimed to compare the efficacy and safety of the afatinib, an irreversible inhibitor of ErbB family receptor, and first-generation TKIs in real-world patients. Materials and methods We included advanced nonsmall cell lung cancer (NSCLC) patients who had EGFR exon 19del mutation and treated with afatinib or first-generation TKIs as upfront treatment between 2016 and 2020. All patient's information was collected retrospectively. The study cohort was divided as afatinib arm and erlotinib/gefitinib arm. Results A total of 283 patients at the 24 oncology centers were included. The 89 and 193 of whom were treated with afatinib and erlotinib/gefitinib, respectively. After 12.9 months (mo) of follow-up, the median PFS was statistically longer in the afatinib arm than erlotinib/gefitinib arm (19.3 mo vs. 11.9 mo, p: 0.046) and the survival advantage was more profound in younger patients (< 65 years). The 24-mo overall survival rate was 76.1% and 49.5% in the afatinib arm and erlotinib/gefitinib arm, respectively. Although all-grade adverse event (AE) rates were similar between the two arms, grade 3-4 AE rates were higher in the afatinib arm (30.7% vs. 15.2%; p: 0.004). Discussion In our real-world study, afatinib has superior survival outcomes despite worse toxicity profile as inconsistent with clinical study results and it is the good upfront treatment option for younger patients and elderly patients who have good performance status.
Keywords: Afatinib; Erlotinib; Exon 19 del; Gefitinib; NSCLC